2022
DOI: 10.1038/s41597-022-01647-1
|View full text |Cite
|
Sign up to set email alerts
|

A large EEG dataset for studying cross-session variability in motor imagery brain-computer interface

Abstract: In building a practical and robust brain-computer interface (BCI), the classification of motor imagery (MI) from electroencephalography (EEG) across multiple days is a long-standing challenge due to the large variability of the EEG signals. We collected a large dataset of MI from 5 different days with 25 subjects, the first open-access dataset to address BCI issues across 5 different days with a large number of subjects. The dataset includes 5 session data from 5 different days (2–3 days apart) for each subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…SPE, SEN, PRE, and F 1 values provided by the WITS-SVM are balanced, which are 74% and 77%, 77%, and 0.75, respectively. The 10-fold CV accuracies obtained from other methods (CSP, FBCSP, FBCNet, EEGNet, and deep ConvNets) reported in a previous study [5] as shown in Table II do not support the 1% statistical significance level ( p ≮ 0.01), whereas those obtained from WIS-SVM, WTS-SVM, and WTIS-SVM do.…”
Section: Within-session Classification Resultsmentioning
confidence: 61%
See 4 more Smart Citations
“…SPE, SEN, PRE, and F 1 values provided by the WITS-SVM are balanced, which are 74% and 77%, 77%, and 0.75, respectively. The 10-fold CV accuracies obtained from other methods (CSP, FBCSP, FBCNet, EEGNet, and deep ConvNets) reported in a previous study [5] as shown in Table II do not support the 1% statistical significance level ( p ≮ 0.01), whereas those obtained from WIS-SVM, WTS-SVM, and WTIS-SVM do.…”
Section: Within-session Classification Resultsmentioning
confidence: 61%
“…Figure 6 shows the training progresses of the LSTM and Bi-LSTM, in which convergences were reached at early stages. The 10-fold CV results produced from CSP, FBCSP, FBCNet, EEGNet, and deep ConvNets as shown in Table II were originally reported in reference [5]. Table III shows the 95% confidence intervals of the mean accuracies computed from the t-test of 10-fold CV obtained from the SVM-based classifiers using wavelet scattering features of the EGG signals, FRPs of the EGG signals, and fusion of two SVM-based classifiers.…”
Section: Within-session Classification Resultsmentioning
confidence: 99%
See 3 more Smart Citations